EFEKTIVITAS INTERVENSI PSIKOEDUKASI DIGITAL BERBASIS INSTAGRAM TERHADAP PENURUNAN TINGKAT STRES - Kasmi; Rapikah; Alawiyah, Desi; Syamirwan (Universitas Islam Ahmad Dahlan, 2026)
This study aims to examine the effectiveness of Instagram-based digital psychoeducation in reducing stress levels among followers of the @dearcounseling account. A pre-experimental method with a one-group pretest–posttest design was employed. The participants consisted of 40 individuals selected through purposive sampling, with criteria including moderate to high stress levels and willingness to participate in the intervention program. The research instrument was a 30-item stress questionnaire that demonstrated strong validity and reliability (Cronbach’s Alpha = 0.885). The intervention, referred to as the stress defeater program, was delivered through educational content and cyber counseling services via Instagram. The results indicate a significant reduction in participants’ stress levels following the intervention, as reflected in the decrease of the average score from 79 in the pretest to 48 in the posttest. Statistical analysis using the Wilcoxon test revealed an Asymp. Sig value of 0.00 (< 0.05), confirming that the Instagram-based digital psychoeducation intervention was effective in lowering stress levels. These findings suggest that social media platforms can serve as innovative, accessible, and relevant tools for psychoeducation and cyber counseling to promote mental well-being in the digital era